2009
DOI: 10.1016/j.ejcts.2009.03.045
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic filling index: a novel parameter to monitor circulatory filling during minimized extracorporeal bypass

Abstract: The dynamic filling index can detect small changes in venous return and drainable volume which remain unrevealed by routinely recorded parameters. This index could be a valuable tool to monitor and control circulatory filling in individual patients supported by minimized extracorporeal bypass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Therefore, changes in central venous pressure may in some cases not reflect true changes in cardiac preload. The DFI is a measure of on-pump venous volume [7], and changes in DFI during reduced unloading (i.e. reduced ELS flow) could be a more reliable measure than central venous pressure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, changes in central venous pressure may in some cases not reflect true changes in cardiac preload. The DFI is a measure of on-pump venous volume [7], and changes in DFI during reduced unloading (i.e. reduced ELS flow) could be a more reliable measure than central venous pressure.…”
Section: Discussionmentioning
confidence: 99%
“…DFI measurement uses periodical, transient reductions (-100 rpm) of pump speed, each lasting approximately 10 seconds, superimposed on the steady state pump speed. The resultant changes in bypass flow are used to calculate the DFI as Δflow/Δspeed (Figure 3 in [7]). When venous volume increases the DFI increases, and vice versa.…”
Section: Introductionmentioning
confidence: 99%
“…After stabilization of bypass flow, manual pump control was switched to computer control and an initial DFI value was measured using three consecutive pump speed manipulations. 12 The DFI threshold was calculated as DFI threshold =½ * DFI initial , and entered into the program. An acute reduction in DV was induced by acute withdrawal of 0.5 litres of blood from the circulation (approximately 10-15% of the total blood volume) via the ELS, using the arterial line.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…10 In a recent study, we demonstrated that small changes in DV, as reflected by the slope of the speed-flow curve (Figure 1 right) can be determined by measuring the dynamic filling index (DFI). 12 This index proved more sensitive to changes in DV than direct haemodynamic and pump-related parameters. Continuous monitoring of DV during ELS provides the possibility of running a reserve-driven control scheme, based on what flow the ELS circuit may deliver at a certain instant rather than what the circuit ideally should deliver (demand-driven).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation